Strategies for Development of Energy Services Companies in Iran - Jafari, Hamed Houri (International Journal of Energy Economics and Policy, 2018)
During the recent decades, Energy Services Companies (ESCOs) have played an important role in energy management and building an appropriate tool for performing energy policies, especially in the case of existence of energy saving potentials in the energy system. These companies have been established in Iran as well and are running now due to the crucial need to energy efficiency improvement in the country. Since extending the markets and activities of these companies needs legislative infrastructures and governmental support, the matter is that how they should be reinforced with these facilities in Iran in order to be involved in energy optimization projects in the post-sanction situation. In this study, ESCO mechanism development strategies in interacting with its internal and external environment are represented. For this purpose, an analytical method based on the identification and evaluation of weaknesses and strengths as well as threats and opportunities of this mechanism is used due to advance the performance of this industry. The obtained results from the evaluation of ESCO mechanism development show the higher scores for external factors in comparison with the internal ones. The SWOT analysis indicates that the appropriate strategy for developing ESCO mechanism in Iran is WO strategy. According to this strategy, the goal of ESCO industry is to reduce weaknesses and to increase opportunities. Keywords: Strategy, Energy Services Company (ESCO), Internal and External Factors, SWOT Analysis JEL Classification: Q40